Service co-production with customers in the framework of service-dominant logic in application to the hotel industry in Tromsø, Northern Norway - Kopanitsa, Kristina (UiT The Arctic University of Norway, 2016)
This Master’s research introduces the concept of service co-production with customers in the framework of service-dominant (S-D) logic as a research paradigm in marketing management. The concept of service co-production was integrated into a tourism management setting and researched in application to the hotel industry in Tromsø, Northern Norway. The aim of this Master’s research was to investigate to investigate whether service co-production with customers is a part of the service/services of a 3 and 4 star chain of hotels in Tromsø, Northern Norway. Thus, six hotel managers of the hotels chosen as research participants were interviewed. The results showed that five of six hotels demonstrate cases of service co-production with customers where customers play an active role in being co-producers of a particular service/services. Service co-production with customers is represented, predominantly, in the form of self-service/services. The extent of service co-production with customers and the aims of its implementation depend on belonging of hotels to budget/full-service hotel category. Hands on managerial implications are provided in the closing part of the paper. ORIGINALITY The thesis show industry specific research of service co-production with customers and has a clear focus on a narrow geographical location. The specificity of the thesis is that the categories of analysis of service co-production as applied in the hotels in Tromsø were theoretically predefined. However, in the process of data analysis, the category of Firm-Driven Service innovations emerged that was not predefined theoretically.